2017
DOI: 10.1021/acsomega.7b00451
|View full text |Cite
|
Sign up to set email alerts
|

In Search of NPY Y4R Antagonists: Incorporation of Carbamoylated Arginine, Aza-Amino Acids, or d-Amino Acids into Oligopeptides Derived from the C-Termini of the Endogenous Agonists

Abstract: The cross-linked pentapeptides (2R,7R)-diaminooctanedioyl-bis(Tyr-Arg-Leu-Arg-Tyr-amide) ((2R,7R)-BVD-74D, (2R,7R)-1) and octanedioyl-bis(Tyr-Arg-Leu-Arg-Tyr-amide) (2) as well as the pentapeptide Ac-Tyr-Arg-Leu-Arg-Tyr-amide (3) were previously described as neuropeptide Y Y4 receptor (Y4R) partial agonists. Here, we report on a series of analogues of (2R,7R)-1 and 2 in which Arg2, Leu3, or Arg4 were replaced by the respective aza-amino acids. The replacement of Arg2 in 3 with a carbamoylated arginine building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(52 citation statements)
references
References 36 publications
0
52
0
Order By: Relevance
“…Aiming at the development of small-molecule probes to selectively target the human Y 4 R, approximately 77 000 compounds were tested by high-throughput screening (HTS). We recently reported on the discovery of Y 4 R positive allosteric modulators (PAM) from this experiment. , In comparison to PAMs and agonists, the hit rate of negative allosteric modulators (NAM) and antagonists was very low (0.022%, Table S1, Supporting Information), reflecting the challenges in the development of Y 4 R antagonists. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Aiming at the development of small-molecule probes to selectively target the human Y 4 R, approximately 77 000 compounds were tested by high-throughput screening (HTS). We recently reported on the discovery of Y 4 R positive allosteric modulators (PAM) from this experiment. , In comparison to PAMs and agonists, the hit rate of negative allosteric modulators (NAM) and antagonists was very low (0.022%, Table S1, Supporting Information), reflecting the challenges in the development of Y 4 R antagonists. ,, …”
Section: Introductionmentioning
confidence: 99%
“… a Determined by competition binding with [ 3 H] 4 at intact HT-29 colon carcinoma cells. b Determined by competition binding with [ 3 H] 6 at intact CHO-hY 4 R-mtAEQ-G qi5 cells. Presented are mean p K i values ± SEM and corresponding mean K i values from three ( 19 , 20 , 27 , and 28 ) or four ( 21 and 22 ) independent experiments (performed in triplicate). c K i value reported by Schindler et al d K i value reported by Kuhn et al n.a. : not applicable. …”
mentioning
confidence: 97%
“…Recently, we reported on a labeling strategy for peptidic receptor ligands based on the N ω -carbamoylated amino-functionalized arginine building blocks 1 and 2 (Figure ), which were incorporated into peptide ligands of G-protein coupled receptors (GPCRs) of different GPCR families. , Unlike recently reported N ω -alkylated arginines, also tolerated in biologically active peptides, the incorporation of 1 and 2 into peptides is feasible by standard Fmoc-strategy solid-phase peptide synthesis (SPPS), leading to amino-functionalized peptides, which are suited, e.g., for conjugation with amino-reactive fluorescent dyes or radionuclide-bearing moieties. , Two examples of radiolabeled peptidic receptor ligands ([ 3 H] 4 and [ 3 H] 6 ), obtained from the parent peptides 3 and 5 by replacement of arginine with an N ω -carbamoylated arginine derived from 1 , are shown in Figure . The radioligands [ 3 H] 4 and [ 3 H] 6 proved to be useful molecular tools. ,, It should be noted that the weakly basic (p K a : 7–8) carbamoylguanidine moiety of N ω -carbamoylated arginines exhibits, in contrast to N -acylated guanidines, high chemical stability . Peptide conjugation or labeling based on amino-functionalized N ω -carbamoylated arginines, derived from arginine derivatives such as 1 or 2 (cf.…”
mentioning
confidence: 99%
See 2 more Smart Citations